Análise de biomarcadores em jundiás (Rhamdia quelen) expostos in situ como uma ferramenta de avaliação ambiental - Severo, Eduardo Stringini (2017)
Aquatic ecosystems are affected by the use of agrochemicals in agricultural areas near rivers. To evaluate possible impacts, studies with animals that inhabit these ecosystems are needed. In situ exposure is one way of assessing possible damage to ecosystems. The aim of this study was to investigate the use of Rhamdia quelen as a bioindicator through its in situ exposure. Group of 10 fishes were transported and placed in cages at three sites (S1, S2 and S3) of the Vacacaí river in the city of São Gabriel, Rio Grande do Sul. After the exposure period of 96 hours, fish were euthanized and brain, gill, liver and muscle were removed for biochemical assays. Biomarkers of oxidative damage as thiobarbituric acid reactive substances (TBARS) and protein carbonylation (PC), biomarker of neurotoxicity as the acetylcholinesterase enzyme (AChE) and antioxidant parameters such as glutathione s-transferase (GST), superoxide dismutase (SOD), catalase (CAT), antioxidant capacity against peroxyl radicals (ACAP) and non-protein thiols (NPSH) were evaluated. The calculation of the Integrated Biomark Response Index (IBR) was used to aid in the interpretation of the results. There was a decrease in AChE in brain of exposed fishes in the three studied sites (S1, S2 and S3). In addition, it decreased levels of TBARS in the brain and increased PC in the brain, liver and gills in S2 and S3. SOD activity decreased at all site in the gills and CAT increased at S3. The increase in GST was mainly observed in the liver at all three sites. ACAP increased in S3. The IBR calculation showed a higher value in S2, followed by S3 and S1. Rhamdia quelen has been shown to be an excellent bioindicator for use in in situ experiments. The use of biomarkers with the help of the IBR proved to be very useful for the results of the study.